Omentin1 ameliorates myocardial ischemia-induced heart failure via SIRT3/FOXO3a-dependent mitochondrial dynamical homeostasis and mitophagy - Hu, Jingui; Liu, Tao; Fu, Fei; Cui, Zekun; Lai, Qiong; Zhang, Yuanyuan; Yu, Boyang; Liu, Fuming; Kou, Junping; Li, Fang (Journal of translational medicine, 2022)
Background Adipose tissue-derived adipokines are involved in various crosstalk between adipose tissue and other organs. Omentin1, a novel adipokine, exerts vital roles in the maintenance of body metabolism, insulin resistance and the like. However, the protective effect of omentin1 in myocardial ischemia (MI)-induced heart failure (HF) and its specific mechanism remains unclear and to be elucidated. Methods The model of MI-induced HF mice and oxygen glucose deprivation (OGD)-injured cardiomyocytes were performed. Mice with overexpression of omentin1 were constructed by a fat-specific adeno-associated virus (AAV) vector system. Results We demonstrated that circulating omentin1 level diminished in HF patients compared with healthy subjects. Furthermore, the fat-specific overexpression of omentin1 ameliorated cardiac function, cardiac hypertrophy, infarct size and cardiac pathological features, and also enhanced SIRT3/FOXO3a signaling in HF mice. Additionally, administration with AAV-omentin1 increased mitochondrial fusion and decreased mitochondrial fission in HF mice, as evidenced by up-regulated expression of Mfn2 and OPA1, and downregulation of p-Drp1(Ser616). Then, it also promoted PINK1/Parkin-dependent mitophagy. Simultaneously, treatment with recombinant omentin1 strengthened OGD-injured cardiomyocyte viability, restrained LDH release, and enhanced the mitochondrial accumulation of SIRT3 and nucleus transduction of FOXO3a. Besides, omentin1 also ameliorated unbalanced mitochondrial fusion-fission dynamics and activated mitophagy, thereby, improving the damaged mitochondria morphology and controlling mitochondrial quality in OGD-injured cardiomyocytes. Interestingly, SIRT3 played an important role in the improvement effects of omentin1 on mitochondrial function, unbalanced mitochondrial fusion-fission dynamics and mitophagy. Conclusion Omentin1 improves MI-induced HF and myocardial injury by maintaining mitochondrial dynamical homeostasis and activating mitophagy via upregulation of SIRT3/FOXO3a signaling. This study provides evidence for further application of omentin1 in cardiovascular diseases from the perspective of crosstalk between heart and adipose tissue. Keywords: Omentin1, Heart failure, Sirtuin 3, Mitochondrial dynamical homeostasis, Mitophagy, Heart-adipose crosstalk